Iqbal’s ideas for a dynamic and sustainable ummah: a way forward - Abdul Razak, Mohd Abbas (2011)
During the peak of the Islamic civilization, Muslims were in the forefront in the areas of philosophy, mathematics, astronomy, physical and social sciences. The fall of Baghdad in 1258 marked the decline of the Islamic civilization and intellectualism. As the Islamic empires fell one after another, starting with Baghdad, this left the Muslims in a pathetic condition, hardly able to regain the prestigious position once they held on the world stage during their heydays. The internal conflicts within the Ummah also in a way failed them from making any significant contribution during the Great Industrial Revolution that happened in the West. Colonization of the Muslim territories during the nineteenth century to some extent deprived them the success of reconstructing and regaining their lost territory in the area of scholastic works. The feeling of defeatism made some quarters within the Islamic Ummah to abandon this worldly aspect of their lives to solely focus on spirituality, leaving the scientific investigation and exploration to the other communities of the world to deal with. Iqbal who was a prominent Muslim philosopher and thinker of the nineteenth century made the clarion call to the Ummah that the spirit of the Qur’an is not only spiritual but also scientific. In his observation, he saw that the Zikr (spirituality) was in the East, particularly with the Muslims, and Fikr (knowledge and the scientific investigations) was with the people in the West. For him the Qur’an is the revealed book of Allah and the universe is the open book of Allah. In Iqbal’s view, in order for the Muslims to be dynamic, prolific, creative and innovative living in the modern world, they have to make a marriage between the Zikr and Fikr found in the Qur’an. In the light of the preceding reality, this paper intends to explore further Iqbal’s ideas on how the Muslims should propel themselves to make this world a better place for themselves and for others. Very precisely, the sort of attitude they should have in dealing with the West in terms of its science and technology for the sustainability of the Islamic Ummah.